2015
DOI: 10.1098/rspb.2015.2257
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of dinitrogen fixation in sustaining coral productivity under oligotrophic conditions

Abstract: Functional traits define species by their ecological role in the ecosystem. Animals themselves are host–microbe ecosystems (holobionts), and the application of ecophysiological approaches can help to understand their functioning. In hard coral holobionts, communities of dinitrogen (N 2 )-fixing prokaryotes (diazotrophs) may contribute a functional trait by providing bioavailable nitrogen (N) that could sustain coral productivity under oligotrophic conditions. This study quantified N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 49 publications
7
116
0
Order By: Relevance
“…Fixation of dinitrogen by these bacteria is an important functional process for corals thriving in oligotrophic tropical environments as they can provide up to 15% of new nitrogen to corals (Bednarz et al, 2017). Increases in the abundance and diversity of nitrogen-fixing bacteria in coral tissue has been observed previously under elevated temperatures (Santos et al, 2014;Cardini et al, 2015Cardini et al, , 2016 and between winter and summer (Cai et al, 2018). We also observed a higher abundance of a Candidatus Amoebophilus bacterium in summer compared to winter.…”
Section: Seasonality Has Higher Impact On Coral Holobiont Than Uv Radsupporting
confidence: 65%
See 1 more Smart Citation
“…Fixation of dinitrogen by these bacteria is an important functional process for corals thriving in oligotrophic tropical environments as they can provide up to 15% of new nitrogen to corals (Bednarz et al, 2017). Increases in the abundance and diversity of nitrogen-fixing bacteria in coral tissue has been observed previously under elevated temperatures (Santos et al, 2014;Cardini et al, 2015Cardini et al, , 2016 and between winter and summer (Cai et al, 2018). We also observed a higher abundance of a Candidatus Amoebophilus bacterium in summer compared to winter.…”
Section: Seasonality Has Higher Impact On Coral Holobiont Than Uv Radsupporting
confidence: 65%
“…Utilization of moderate doses of UVR (mostly UV-A) as a source of energy for photosynthesis has been previously observed in phytoplankton species (Gao et al, 2007;Wu et al, 2009), and our results suggest this may also be applicable to Symbiodinium in corals. On the contrary, in summer, exposure to naturally high UVR levels led to a significant reduction in Symbiodinium photosynthetic efficiency, which may have been compensated for through an increase in chlorophyll content, as previously observed (Cardini et al, 2015). Previous studies have also shown that the lowest photosynthetic yield (F v /F m ) or rETR max values of diverse scleractinian coral species coincide with the highest irradiance and temperature levels on the reef, and are caused by damage to the photosystems (Fitt et al, 2000;Warner et al, 2002;Winter et al, 2016).…”
Section: Seasonality Has Higher Impact On Coral Holobiont Than Uv Radmentioning
confidence: 60%
“…Therefore, it was suggested that the association with diazotrophs is particularly beneficial to the nutrition of corals during periods of low nutrient availability in the surrounding seawater. The level of coral-associated N 2 fixation activity also varies depending on the environmental conditions with highest N 2 fixation rates during nutrient-depleted conditions indicating a potentially higher DDN availability for the coral symbiosis (Bednarz et al, 2015a;Cardini et al, 2015). A mechanistic nitrogen flux model shows that the uptake of dissolved nitrogen from the seawater can provide 149% of the required nitrogen but decreases down to 18% when dissolved nitrogen concentrations are low .…”
Section: Contribution To Nitrogen Nutritionmentioning
confidence: 99%
“…Heterotrophic feeding on particulate nitrogen sources was considered to satisfy most of the coral's nitrogen demand (Houlbrèque and FerrierPagès, 2009), but also the uptake of dissolved nitrogen in the form of NH + 4 (42%), nitrate (34%), dissolved free amino acids (21%) and urea (3%) together can contribute up to 100% to the coral's nitrogen demand (Grover and Maguer, 2002;Grover et al, 2003Grover et al, , 2006Grover et al, , 2008. However, the uptake of external nitrogen sources is concentration-dependent and coral reefs experience strong seasonal and diel variation in dissolved and particulate nutrient availabilities (Grover and Maguer, 2002;Cardini et al, 2015). Therefore, it was suggested that the association with diazotrophs is particularly beneficial to the nutrition of corals during periods of low nutrient availability in the surrounding seawater.…”
Section: Contribution To Nitrogen Nutritionmentioning
confidence: 99%
“…Photosynthetic sponges can contribute to increase primary productivity especially in oligothrophic ecosystems (Steindler et al 2002;Wilkinson 1983). Davy et al (2002) stated that most of the symbioses studied occurred in tropical nutrient-poor waters (Cardini et al 2015), where nitrogen required for algal growth is probably supplied from sponge catabolism. However, Lemloh et al (2009) demonstrated that percentages of photosynthetic sponges in temperate Western Australia were comparable with those of the coral reefs, suggesting that these relationships are underestimated and poorly investigated, especially outside the tropical areas.…”
Section: And Even Caddisfliesmentioning
confidence: 98%